PENERAPAN METODE DISCOVERY UNTUK MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN PROSES PENGOLAHAN DAN PENGAWETAN SISWA KELAS X SMK NEGERI 2 PINRANG - Abdullah, Edi; Syam, Husain; Latief, Nurlaela (Jurnal Pendidikan Teknologi Pertanian, 2016)
This research is a class room action research that aims to improve the student learning  achievements in processing and desiccation subject through particular discovery method at the 1st  year class of SMK 2 Pinrang in 2014-2015 academic year, with 28 students. This study was conducted in two cycles, each cycle consists of planning, observation, and reflection stage. The treatment which has been done in first and second cycle was discovery method. The result showed that implementing of discovery method can improve student  learning achievement. In the first cycle, the competence of student was 82,14% in average acquisition percentage and it has increased to 96.42% in the second cycle. The value acquisition in the second cycle was assumed completed according in KTSP (Curriculum Education Unit) ≥ 75. Thus it can be said that the implementing of discovery method can improve academic achievement either in theory, practices and the way of learning